Quo Vadis Micro, Small, and Medium Enterprises Competitive Advantage: Evidence from Indonesia - Wicaksono, Baghas Budi; Wibowo, FX Pudjo (Poltanesa, 2023)
This research aims to identify the influence of personal network variables and product quality on the competitive advantage of MSMEs through moderating variables. The data used in this research is primary data in the form of a questionnaire filled in by 167 respondents who have heterogeneity in gender, age, education and information about business. Researchers use Structural Equation Modeling as a method for extracting data. The research results show that all independent and moderating variables have a positive influence on the competitive advantage variable of MSMEs. This is indicated by a t-statistic value that is greater than the t-table with a p-value < 0.05. The validity and reliability indicators through outer loading also show values ​​above 0.6 on average. Therefore, the implications of this research are as follows: The government as a stakeholder must be able to bridge the community to be able to access business capital through networks, business incubators, academia, media, and society The community must have good literacy regarding the quality of a product and product knowledge so that it can have competitiveness in numerous free MSME’s Market, Academics and researchers are expected to accelerate the down streaming of products so that they have greater benefits for the informal sector economy.